2009
DOI: 10.1021/jm801532e
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure−Activity Analysis of Isoform-Selective Retinoic Acid Receptor β Ligands

Abstract: We recently discovered the isoform selective RAR beta 2 ligand 4'-octyl-4-biphenylcarboxylic acid (3, AC-55649). Although 3 is highly potent at RAR beta 2 and displays excellent selectivity, solubility issues make it unsuitable for drug development. Herein we describe the exploration of the SAR in a biphenyl and a phenylthiazole series of analogues of 3. This ultimately led to the design of 28, a novel, orally available ligand with excellent isoform selectivity for the RAR beta 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…[29] RARb-selective agonists have been described, [23] including a potent and selective agonist of the RARb2 isoform (one of the four isoforms originated by differential use of two promoters and alternative splicing) [1] with druglike properties and good oral bioavailability in rats. [53,54] RARb subtype-selective antagonists and inverse agonists are, however, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[29] RARb-selective agonists have been described, [23] including a potent and selective agonist of the RARb2 isoform (one of the four isoforms originated by differential use of two promoters and alternative splicing) [1] with druglike properties and good oral bioavailability in rats. [53,54] RARb subtype-selective antagonists and inverse agonists are, however, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of 10 with the selective RARβ agonist AC-261066 8 showed that in our hands, 10 is a more potent and selective RARβ agonist (Table 4). Whilst compound 10 is marginally less potent than CD 2019, it has a better selectivity for RARβ over RARα and RARγ and is over two orders of magnitude less lipophilic.…”
mentioning
confidence: 69%
“…The lower EC 50 (0.03 µM) value observed for 9‐cis RA suggests that it is a more efficient ligand than retinal for the RARs. Although it is possible that retinal directly binds to the RARs, albeit at a lower affinity, this possibility is unlikely as retinaldehyde lacks the critical carboxylic acid moiety that hydrogen bonds with Arg278 and Ser289 residues of the RAR (Lund et al, 2005, 2009). These data suggest that retinaldehyde is being oxidized by RALDH enzyme(s) to retinoic acid, which in turn is driving expression from the RARE‐promoter complex (Duester et al, 2003).…”
Section: Resultsmentioning
confidence: 99%